Contemporary views on human aging and longevity - Chmielewski, Piotr; Borysławski, Krzysztof; Strzelec, Bartłomiej (Anthropological Review, 2016)
Aging is currently stimulating intense interest of both researchers and the general public. In developed countries, the average life expectancy has increased by roughly 30 years within the last century, and human senescence has been delayed by around a decade. Although aging is arguably the most familiar aspect of human biology, its proximate and ultimate causes have not been elucidated fully and understood yet. Nowadays there are two main approaches to the ultimate causes of aging. These are deterministic and stochastic models. The proximate theories constitute a distinct group of explanations. They focus on mechanistic causes of aging. In this view, there is no reason to believe that there is only one biological mechanism responsible for aging. The aging process is highly complex and results from an accumulation of random molecular damage. Currently, the disposable soma theory (DST), proposed by Thomas Kirkwood, is the most influential and coherent line of reasoning in biogerontology. This model does not postulate any particular mechanism underpinning somatic defense. Therefore, it is compatible with various models, including mechanistic and evolutionary explanations. Recently, however, an interesting theory of hyper-function of mTOR as a more direct cause of aging has been formulated by Mikhail Blagosklonny, offering an entirely different approach to numerous problems and paradoxes in current biogerontology. In this view, aging is quasi-programmed, which means that it is an aimless continuation of developmental growth. This mTOR-centric model allows the prediction of completely new relationships. The aim of this article is to present and compare the views of both parties in the dispute, based on the results of some recent experimental studies, and the contemporary knowledge of selected major aspects of human aging and longevity.